Efficacy of Methyl-eugenol as Male Attractant for Dacus dorsalis Hendel (Diptera: Tephritidae) - Ibrahim, Abdul Ghani; Hashim, A. Ghani (1980)
Dacus dorsalis Hendel is the predominant species of fruit-fly (99.8%) found in a carambola orchard. Population level was found to be correlated (r = 0.56) with rainfall. Infestation of fruits began 29 days after fruit set. Laboratory studies show that among the three species of fruitflies tested for attractiveness to methyl eugenol, male of D. dorsalis and D. umbrosus showed no significant difference but both are significantly different (p < 0.05) with D. cucurbitae. Virgin adult males of D. dorsalis more than 20 days old were greatly attracted to methyl eugenol